Relationship between reduced serum ceruloplasmin levels and executive dysfunction in hospitalized schizophrenia patients - Kuang, Dan; Wei, Hongkai; Qin, Wei (Frontiers in Psychiatry, 2025)
ObjectiveExecutive dysfunction is a widespread and complex manifestation in schizophrenia, significantly impairing patients’ cognitive and functional outcomes. Despite extensive research, specific biomarkers associated with this dysfunction remain unidentified. Serum ceruloplasmin (Cp), a copper-binding protein involved in iron metabolism and oxidative stress regulation, has recently been implicated in neurological conditions. This study aims to investigate the relationship between reduced serum Cp levels and executive dysfunction in hospitalized schizophrenia patients, providing insights into potential biomarkers and therapeutic targets.MethodsA total of 95 schizophrenia inpatients treated at Shaoxing Seventh People’s Hospital from January 2023 to December 2024 were enrolled. Patients were divided into two subgroups based on serum Cp concentrations: 48 patients with reduced Cp levels (SC1 group, Cp < 200 mg/L) and 47 patients with normal Cp levels (SC2 group, 200-600 mg/L). Additionally, 42 age- and gender-matched healthy individuals served as the control group. Blood samples were collected for Cp measurement using an automated biochemical analyzer. The severity of psychiatric symptoms was assessed using the Positive and Negative Syndrome Scale (PANSS), while the Tower of London (TOL) test was employed to evaluate executive function. Statistical analyses included one-way ANOVA and Spearman’s correlation to examine group differences and relationships between Cp levels and cognitive performance.ResultsSignificant differences in serum Cp levels were observed among the SC1, SC2, and control groups (P < 0.01). Executive function, assessed via the TOL test, showed no significant difference between the SC1 and SC2 groups (P > 0.05); however, both groups exhibited significantly impaired performance compared to the control group (P < 0.001). A strong positive correlation was identified between Cp levels and TOL performance in the SC1 group (r = 0.890, P < 0.001), particularly in simpler and moderately complex tasks.ConclusionBased on the existing evidence of widespread cognitive impairment in schizophrenia patients, this study delves deeper into its potential causes. We found that regardless of whether schizophrenia patients had normal or low serum ceruloplasmin (CP) levels, their executive function was significantly lower than that of healthy individuals. Furthermore, a correlation analysis showed a significant link between CP levels and executive dysfunction in schizophrenia patients with decreased CP levels. Our study suggests that low CP levels may aggravate executive dysfunction, indicating that CP deficiency might be a biological marker of executive dysfunction in schizophrenia.